PENGEMBANGAN MEDIA PEMBELAJARAN POP UP BOOK DIGITAL PADA MATA PELAJARAN IPAS KELAS V SEKOLAH DASAR - Astrid Rahmadani, Novitri; Ulya Akmal, Atika; Fitria, Yanti; Amini, Risda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Low student interest and engagement, as well as poor learning outcomes in IPAS (Natural and Social Sciences), stem from a lack of variety and innovation in the instructional media employed. Digital pop-up books had not previously been used as learning media for the fifth-grade IPAS subject addressed in this study. The research aimed to develop a digital pop-up book as a learning medium that meets criteria for validity, practicality, and effectiveness. “This research and development study utilized the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation.”The findings revealed a high level of validity for the digital pop-up book (validity score: 91.67%). At the first trial school, SDN 47 Korong Gadang, results showed a practicality score of 94% based on teacher feedback “highly practical” and 89.90% based on student feedback (highly practical); an N-gain score of 65% “highly effective”; and a student participation rate of 78% “active”. In the second trial at SDN 09 Korong Gadang, the N-gain score reached 68% “moderate effectiveness”, student participation was 80% “active”, and practicality ratings were 90% from teachers (highly practical) and 88.13% from students “highly practical”. Additionally, research at SDN 34 Kuranji showed an N-gain score of 70% “moderate effectiveness”, student participation of 83% “highly active”, and practicality ratings of 96% from teachers (highly practical) and 98.10% from students “highly practical”. Thus, the digital pop-up book proved to be a valid, practical, and effective learning medium.